The iron condor strategy in financial risk management - Dziawgo, Ewa (Strategia iron condor w zarządzaniu ryzykiem finansowym, 2020)
The iron condor strategy is a complex option strategy that combines two option spread strategies. The design of this strategy makes it possible to make profits from underlying instruments whose prices are in horizontal trends over a certain period. The research objective of the article is to analyse the risk resulting from the iron condor strategy. The article presents the structure of the strategy, the pricing model, the impact of the price of the underlying instrument on the value of the strategy and on the value of the delta, gamma, vega, and theta ratios. These ratios are measures of the risk of option contracts. The empirical illustration contained in the article is based on the simulation of the valuation of currency options issued in EUR/PLN
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 33-44
Keywords: financial instruments; option; option strategy; measures of the risk of option; instrumenty finansowe; opcje; strategie opcyjne; miary ryzyka opcji